Seroprevalence and risk factors associated with Porcine Cysticercosis and Trichinella spiralis in backyard pigs in Bucaramanga province, Colombia - pinilla, juan; Giesen, Rietge; florez, angel (Archives of Veterinary Science, 2023)
A large number of the parasitic agents that alter the health of swine could be spread to humans, especially in backyard conditions, and, many times, cause difficulties in public health and food security. This investigation was conducted to determine the seroprevalence and risk factors associated with swine cysticercosis and Trichinella spiralis in backyard pigs in the Bucaramanga province of Colombia. A total of 380 serum samples were used for the search for Tr. spiralis and Tenia solium antibodies using the ELISA technique. The seroprevalence of T. solium cysticercosis infection was 40.5%, whilst anti-Tr. spiralis antibodies were not observed in the processed samples. Regarding risk factors, free-ranging pigs and non-dewormed pigs showed almost 3 (OR=2.9; P ≤ 0.05) and 2.7 (OR=2.7; P ≤ 0.05) times more risk of presenting antibodies against T. solium cysticercosis, respectively. The seroprevalence of swine cysticercosis found in this investigation can be caused by low-quality housing and poor hygiene, increasing the spread of this zoonotic parasite infection among swine and humans. No positive samples for Tr. spiralis were observed. The variables access to latrines and deworming of pigs were presented as the risk of infection for cysticercosis by T. solium, this could increase the probability of infection risk of parasites with zoonotic potential between pigs and humans.